MINIMIZING NUMBER OF DEFECTS IN NICKEL PLATING PROCESS USING FACTORIAL DESIGN - Baharuddin, Nurul Qasturi; Sukarma, Lukman; Mohamad, Effendi (Journal of Advanced Manufacturing Technology (JAMT), 2016)
Product defect may have a serious problem in any manufacturing company because they increase the production cost due to rework, delays, waste of time and material. The purpose of this study is to investigate significant factors and their interaction in order to find the optimal setting that can reduce the numbers of defect in nickel plating line. Factorial design has been used as the experimental design technique to identify the critical factors to be controlled. This experiment inveestigated three different factors and full factorial design experiment was applied. The data collected and analyzed by using Design Expert software. This study used ANOVA to find the most significant factors. The result suggested that only one main factor (BCS) and one interaction factor (BCS and hot COT temperature) affect the number of defect in nickel plating line. The optimum process setting was at 22 g/L of BCS and 50°C of hot COT temperature. A confirmation run using these new settings was conducted which shows a decreasing in the number of defect in nickel plating process